Nicotinamide as a Foundation for Treating Neurodegenerative Disease and Metabolic Disorders - Maiese, Kenneth (Current neurovascular research, 2021)
Neurodegenerative disorders impact more than one billion individuals worldwide and are intimately tied to metabolic disease that can affect another nine hundred individuals throughout the globe. Nicotinamide is a critical agent that may offer fruitful prospects for neurodegenerative diseases and metabolic disorders, such as diabetes mellitus. Nicotinamide protects against multiple toxic environments that include reactive oxygen species exposure, anoxia, excitotoxicity, ethanolinduced neuronal injury, amyloid (Aß) toxicity, age-related vascular disease, mitochondrial dysfunction, insulin resistance, excess lactate production, and loss of glucose homeostasis with pancreatic β-cell dysfunction. However, nicotinamide offers cellular protection in a specific concentration range, with dosing outside of this range leading to detrimental effects. The underlying biological pathways of nicotinamide that involve the silent mating type information regulation 2 homolog 1 (Saccharomyces cerevisiae) (SIRT1), the mechanistic target of rapamycin (mTOR), AMP activated protein kinase (AMPK), and mammalian forkhead transcription factors (FoxOs) may offer insight for the clinical translation of nicotinamide into a safe and efficacious therapy through the modulation of oxidative stress, apoptosis, and autophagy. Nicotinamide is a highly promising target for the development of innovative strategies for neurodegenerative disorders and metabolic disease, but the benefits of this foundation depend greatly on gaining a further understanding of nicotinamide's complex biology.